Adolescents' expectancy–value profiles in school context: The impact of self‐directed learning intervals. Issue 4 (10th April 2022) - Schweder, Sabine; Raufelder, Diana
Abstract: Introduction: Using the situated expectancy–value theory, it becomes possible to explain motivational functioning across alternating learning conditions not only at a particular moment but also over time. The situated expectancy–value theory provides evidence for the critical role of context. The present research examines how adolescents' success expectancies, task values, and effort develop when the conditions of the academic environment change. It also evaluates whether adolescents adopt more adaptive expectancy–value profiles in response to the need‐based nature of self‐directed learning as an extension of regular instruction. Within the self‐directed learning approach under investigation, adolescents take responsibility for their own learning processes. Methods: The present research offers insights into the expectancy–value profiles of 754 German adolescents ( M age = 13.56; SD = 1.2; 49.4% female). A four‐wave study was used to examine perceptions of self‐efficacy, intrinsic value, utility value, and effort. Latent profile analyses and latent transition analyses were employed. Results: Notably, the results provide evidence that expanding instruction via self‐directed learning intervals that occur for 1 week per semester contributes to more favorable expectancy–value profiles within a student's favorite subject. A mixed profile (highly confident, hardly interested) disappeared. Instead, success expectations aligned more closely with adolescents' task values and effort. All profiles settled at a higher level. Conclusions: The findings indicate that instruction that is expanded via self‐directed learning intervals has positive consequences for motivational profiles over time. An initial self‐directed learning episode led to a shift to more interested profile groups. The continuation of a positive trend even after a self‐directed learning interval indicates that adolescents are able to continually adapt their learning to their needs during teacher‐directed instruction. This study provides clues about how to design curricula in a way that counteracts the downward trend in students' motivation to learn.